The Effects of Public Debt, Inflation, and their Interactionon Economic Growth in Developing Countries: Empirical Evidence Based on Difference Panel GMM - Bon , Nguyen Van (Asian Journal of Empirical Research, 2015)
The paper empirically investigates the effects of public debt, inflation and their interaction on growth rate for a whole sample of 60 developing countries and for three sub-samples of developing countries (22 in Asia, 11 in Latin America and 27 in Africa) over the period 1990 – 2014 through the estimation method of difference panel GMM. The estimated results showed that for the whole sample and the sub-sample of Latin America, the effects of public debt and inflation on growth are negative, while their interaction is positive. For the sub-sample of Asia, public debt and inflation have positive effects on growth, whereas their interaction has a negative impact; and for the sub-sample of Africa, the effects of public debt and interaction on growth are negative, whereas the influence of inflation is positive. These results suggest some important implications for governments in these developing countries.